Hubungan Antara Pengetahuan, Pola Konsumsi Dan Pendapatan Terhadap Kurang Energi Kronik (Kek) Pada Calon Pengantin Perempuan Di Puskesmas Kec.Penjaringan Tahun 2023 - Sri Danarti; Indah Sri Wahyuni; Eka Bati Widyaningsih (Indonesian Journal of Midwifery Scientific, 2024)
In Indonesia, there are many cases of SEZ (Chronic Energy Deficiency). The occurrence of SEZ is a condition where the mother suffers from chronic food shortages that can cause health problems for a mother. This study aims to determine the relationship between knowledge, consumption patterns and income on chronic lack of energy (SEZ) in brides-to-be at the Penjaringan sub-district health center in 2023. This study used a type of observational research with a descriptive approach. Where the variables studied were measured in the same time using a crossectional research design. Held from January to May 2023 in the working area of the Penjaringan sub-district health center, namely 40 samples with sampling techniques using total sampling, data on knowledge, consumption patterns and income were obtained through interviews using questionnaires. The results of this univariate-based study showed that 65% of brides-to-be in the Penjaringan sub-district puskesmas experienced mild chronic energy deficiency (SEZ) and 35% experienced severe SEZ. The bivariate results of knowledge factors related to SEZs in brides-to-be were p = 0.020, consumption patterns p = 0.006, income p = < 0.001.